2018
DOI: 10.1111/tmi.13184
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a cervical high‐grade lesion on cytology or a positive visual inspection with acetic acid among more than 3300 Tanzanian women

Abstract: Objectives Cervical cancer screening by visual inspection with acetic acid (VIA) is a widely used alternative to cytology in developing countries. This study aimed to evaluate risk factors associated with a positive VIA test and with cervical high‐grade lesions on cytology. Methods We conducted a large cross‐sectional study among 3339 women from urban and rural Tanzania. Study participants were interviewed about socio‐demographic, reproductive and lifestyle factors. Blood samples were tested for HIV, and a gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…16 Women who were HR-HPV positive had an almost 100-fold in- 16 and it is suggested that because of an altered immune system, older women are more likely to develop precancerous lesions and cancer. 17 We found an overall HGC prevalence of 3.6%, which is in line with a previous Tanzanian study conducted among a similar study population reporting an HGC prevalence of 3.7%. 17 However, our HGC prevalence rate is considerably higher than the reported global HGC prevalence rates of 0.3%-0.7%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…16 Women who were HR-HPV positive had an almost 100-fold in- 16 and it is suggested that because of an altered immune system, older women are more likely to develop precancerous lesions and cancer. 17 We found an overall HGC prevalence of 3.6%, which is in line with a previous Tanzanian study conducted among a similar study population reporting an HGC prevalence of 3.7%. 17 However, our HGC prevalence rate is considerably higher than the reported global HGC prevalence rates of 0.3%-0.7%.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of HGC varied greatly by age and was highest among HR‐HPV‐positive women aged 50‐60 years, among whom approximately 30% had HGC in comparison with 4% of women aged 25‐29 years. Other studies have also reported increasing HGC rate by age, 16 and it is suggested that because of an altered immune system, older women are more likely to develop precancerous lesions and cancer 17 …”
Section: Discussionmentioning
confidence: 95%
“…Seven studies investigated cervical cancer screening practices in Tanzania, with an emphasis on predictors of accessing such services. Screening methods deployed over the past six years were largely VIA-based, although Pap smears were occasionally used (Baldur-Felskov et al, 2018; Chambuso et al, 2017; Kafuruki et al, 2013; Liu et al, 2016). Multiple publications focused on improving screening programs through strengthening provider training (see Domain V).…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative VIA positivity was 9.2% (n = 4062) (Table 1). HIV infection was significantly associated with precancerous changes, with 16.8% of HIV+ women also VIA+ (523/3122) (Anderson et al, 2015; Bernstein et al, 2018; Dartell et al, 2014; Baldur-Felskov et al, 2018; Masalu et al, 2017; Chambuso et al, 2017; Kafuruki et al, 2013) (Table 2). High grade dysplastic lesions were often inferred by VIA screening results due to infrequency of pathologic confirmation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation